2009
DOI: 10.1007/s00408-009-9183-1
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone and Cyclic AMP Regulate Sodium Phosphate Cotransporter (NaPi-IIb and Pit-1) mRNA and Phosphate Uptake in Rat Alveolar Type II Epithelial Cells

Abstract: Alveolar epithelial type II (AT II) cells need phosphate (Pi) for surfactant synthesis. The Na-dependent (Na(d)) Pi transporters NaPi-IIb and Pit-1 are expressed in lung, but their expression, regulation, and function in AT II cells remain unclear. We studied NaPi-IIb and Pit-1 mRNA expression in cultured AT II cells isolated from adult rat lung, their regulation by agents known to enhance surfactant production, dexamethasone (dex) and dibutyryl cyclic AMP (cAMP), and the effects of dex and cAMP on Na(d) Pi up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…In the intestine, NaPi-2b expression is up-regulated by estrogen, vitamin D 3, and during metabolic acidosis, and the expression is suppressed by glucocorticoids, epidermal growth factor (EGF), and when the vitamin D receptor (VDR) is lacking [ 64 , 66 70 ]. In addition, dexamethasone has been shown to down-regulate mRNA expression of NaPi-2b and decrease the uptake of phosphate in cultured alveolar type II cells from rats [ 71 ]. Contrary to this, NaPi-2b in rat lung was found not to be regulated at the mRNA level by the vitamin D analog ED-71 (1α, 25-dihydroxy-2ß-(3-hydroxypropoxy) vitamin D 3 ) [ 72 ].…”
Section: Etiologymentioning
confidence: 99%
“…In the intestine, NaPi-2b expression is up-regulated by estrogen, vitamin D 3, and during metabolic acidosis, and the expression is suppressed by glucocorticoids, epidermal growth factor (EGF), and when the vitamin D receptor (VDR) is lacking [ 64 , 66 70 ]. In addition, dexamethasone has been shown to down-regulate mRNA expression of NaPi-2b and decrease the uptake of phosphate in cultured alveolar type II cells from rats [ 71 ]. Contrary to this, NaPi-2b in rat lung was found not to be regulated at the mRNA level by the vitamin D analog ED-71 (1α, 25-dihydroxy-2ß-(3-hydroxypropoxy) vitamin D 3 ) [ 72 ].…”
Section: Etiologymentioning
confidence: 99%
“…Experimental evidence eventually showed that these receptors were electrogenic sodium phosphate transporters . Unlike the transporters of the SLC34 family, which are mainly found in the gut and kidneys, PiT transporters are found ubiquitously and are present in bone cells (osteoblast and osteoclasts) and chondrogenic cells, VSMCs, parathyroid cells and hepatic cells as well as gut tissue and kidney tissue . PiT transporters are essential for osteoblastic differentiation.…”
Section: Phosphate Transportersmentioning
confidence: 99%
“…These transporters play a major role in phosphate metabolism balance. Three types of sodium-phosphate cotransporter have been isolated from mammalian cell membranes: type I sodium-dependent phosphate cotransporter (NaPi-I), type II sodium-dependent phosphate cotransporter (NaPi-II), and type II sodium-dependent phosphate cotransporter (NaPi-III); there are 3 types of NaPi-II: type IIa (NaPi-IIa), type IIb (NaPi-IIb), and type IIc (NaPi-IIc) (Jin et al, 2010). Therefore, the goal of present study was to elucidate the correlation between hyperphosphatemia and the Na-Pi cotransporter, as well as to provide an experimental basis for the clinical treatment and research of hyperphosphatemia and related complications.…”
Section: Introductionmentioning
confidence: 99%